Colaboradores - Geraldello, Camilla Silva (Faculdade de Filosofia e Ciências, 2019)
Biografias e emails dos colaboradores desta edição:   Alexandre Fontenelle-Weber Armando Gallo Yahn Filho Bárbara de Abreu Oliveira Beatriz Walid de Magalhães Naddi Bruna Coelho Jaeger Charles Pennaforte Cristina Soreanu Pecequilo Fabiana Oliveira Felipe Bernardo Estre Fernanda de Castro Brandão Martins  Jayme Benvenuto  Lucas Gualberto do Nascimento Monica Esmeralda Bruckmann Maynetto